Optimization of Terminal-Restriction Fragment Length Polymorphism Analysis for Complex Marine Bacterioplankton Communities and Comparison with Denaturing Gradient Gel Electrophoresis - Moeseneder, Markus M. (American Society for Microbiology, 1999)
The potential of terminal-restriction fragment length polymorphism (T-RFLP) and the detection of operational taxonomic units (OTUs) by capillary electrophoresis (CE) to characterize marine bacterioplankton communities was compared with that of denaturing gradient gel electrophoresis (DGGE). A protocol has been developed to optimize the separation and detection of OTUs between 20 and 1,632 bp by using CE and laser-induced fluorescence detection. Additionally, we compared T-RFLP fingerprinting to DGGE optimized for detection of less abundant OTUs. Similar results were obtained with both fingerprinting techniques, although the T-RFLP approach and CE detection of OTUs was more sensitive, as indicated by the higher number of OTUs detected. We tested the T-RFLP fingerprinting technique on complex marine bacterial communities by using the 16S rRNA gene and 16S rRNA as templates for PCR. Samples from the Northern and Middle Adriatic Sea and from the South and North Aegean Sea were compared. Distinct clusters were identifiable for different sampling sites. Thus, this technique is useful for rapid evaluation of the biogeographical distribution and relationships of bacterioplankton communities.